Model-based intensification of CHO cell cultures: One-step strategy from fed-batch to perfusion - Richelle, Anne; Corbett, Brandon; Agarwal, Piyush; Vernersson, Anton; Trygg, Johan; McCready, Chris (Frontiers in Bioengineering and Biotechnology, 2022)
There is a growing interest in continuous processing of the biopharmaceutical industry. However, the technology transfer from traditional batch-based processes is considered a challenge as protocol and tools still remain to be established for their usage at the manufacturing scale. Here, we present a model-based approach to design optimized perfusion cultures of CHO cells using only the knowledge captured during small-scale fed-batch experiments. The novelty of the proposed model lies in the simplicity of its structure. Thanks to the introduction of a new catch-all variable representing a bulk of by-products secreted by the cells during their cultivation, the model was able to successfully predict cellular behavior under different operating modes without changes in its formalism. To our knowledge, this is the first experimentally validated model capable, with a single set of parameters, to capture culture dynamic under different operating modes and at different scales.